The relationship between financial wellness and health status with employees to work after retirement - Sandra Iris, Albert Lunju; Dayang Kartini, Abang Ibrahim (-, 2012)
Nowadays, a lot of employees who have retired continue to work after their retirement age. There are many reasons why retirees choose to work after retirement. The employees that choose to work after retirement would want to develop their career more and it is a good opportunity for them to being offered or continues to work after retirement. As in this study, researcher has identified two factors which have been influenced employees to work after retirement which are the financial wellness and health status. These two factors are the independent variables in this study which affect employees to work after retirement while the dependent variable is work after retirement. This study has been analyzed by using quantitative method. 70 respondents from private sector have been used to conduct the study. The findings and discussion from the study will be discussed and the recommendations are given to the future researcher that would want to conduct further research regarding the other factors that influencing work after retirement.